Continuous pasteurization of egg yolk: Thermophysical properties and process simulation - Gut, JAW; Pinto, J. M.; Gabas, A. L.; Telis-Romero, J. (Blackwell Publishing, 2005)
This article presents empirical correlations to predict the density, specific heat, thermal conductivity and rheological power-law parameters of liquid egg yolk over a temperature range compatible with its industrial thermal processing (0-61 C). Moreover, a mathematical model for a pasteurizer that takes into account the spatial variation of the overall heat transfer coefficient throughout the plate heat exchanger is presented, as are two of its simplified forms. The obtained correlations of thermophysical properties are applied for the simulation of the egg yolk pasteurization, and the obtained temperature profiles are used for evaluating the extent of thermal inactivation. A detailed simulation example shows that there is a considerable deviation between the designed level of heat treatment and that this is predicted through process simulation. It is shown that a reliable mathematical model, combined with specialized thermophysical property correlations, provide a more accurate design of the pasteurization equipment that ensures effective inactivation, while preserving nutritional and sensorial characteristics.